Experimental dataset of a model-scale ship in calm water and wavesUniversity of Southampton Institutional Repository - Saeed Hosseinzadeh; Stephen Turnock; Haesol Lee; Rodolfo Olvera (Data in Brief)
This article presents data derived from a series of experiments conducted on a scaled model ship, examining its performance in both calm water and regular waves. The acquisition of high-quality experimental data is essential for refining Computational Fluid Dynamics (CFD) simulations and modifying analytical methods to evaluate the powering performance of ships. Despite notable advancements in numerical models, there exists a corresponding imperative to elevate the precision of measurements and insights obtained from towing tank tests. Accordingly, a self-propelled model-scale of the KRISO Container Ship (KCS) hull is used to assess hydrodynamic performance of ships and investigate the interaction between the hull, propeller, and rudder. A set of captive model tests is carried out on the single-screw KCS model in the University of Southampton's Boldrewood towing tank. The model-scale experiments are conducted in an offloaded propeller condition at ship's design speed, which is characterised by a specific Froude number of 0.26. Various test configurations are explored, encompassing four rudder angles, five leeway angles, two wave conditions, and two propeller speeds. Throughout the experiments, multiple parameters were recorded, including the wave environment, ship motions, hull forces and moments, propeller thrust and torque, as well as rudder forces and moments. Initial analysis of the data involved comparing the calm water resistance results with previously published experimental data, revealing a favourable agreement. Additionally, video footage captured from two different angles during various runs serves as illustrative samples of the experimental procedures. This comprehensive series of experiments offers a benchmark for future research endeavours, providing a foundation for refining subsequent experiments, validating numerical methods, and enhancing mathematical models.